Turbinas eólicas: modelo, análise, e controle do gerador de indução com dupla alimentação - Marques, Jeferson (2004)
This thesis presents the main concepts and configurations used in wind turbine connected to the grid, as well as, an analysis, design and implementation of the control system for the Doubly Fed Induction Generator (DFIG). The DFIG has been selected since it is the concept frequently adopted by the wind turbine manufactures. In the thesis, it is presented a model of the DFIG in stator flux reference frame that is normally used in DFIG. The main reason for use the stator flux reference frame is that in this referential is possible to control the active and reactive power of the stator circuit independently. However, the main limitation related with the DFIG vector control is the poor damping oscillation of the stator flux. Aiming to study this problem, the impact of the bandwidth of the rotor currents control loop in the stator flux oscillation mode that appears near the voltage grid frequency, is investigated. It is demonstrated that when Rs approaches of the zero, these oscillations can not be controlled by the rotor converter. The proposed controller has an internal current control loop and an external power control loop. As the controllers are usually implemented in a digital signal processor (DSP), a redesign in discrete time to compute the control action with anti-windup is given. Finally, experimental results to validate the controllers design using a 2 kW DFIG and IGBT PWM converter, controlled by the DSP TMS320F241, are presented.